Colposcopy Findings In High-Grade Cervical Precancer Lesion - Andi Friadi (Universitas Andalas, 2020)
Cervical precancer lesion can generally be seen in the transformation zone. Colposcopy allows us to see an image of enlarge precancer lesion in the transformation zone. The colpocopist should consider some important things to determine the appearance of low-grade lesion or high-grade lesion. Two important things are the description of abnormal epithelium and the description of abnormal blood vessels. The description of the abnormal epithelial seen after administration of acetic acid 3-5%, acetowhite looks faster and disappears slower. The “white” lesion is more concentrated like the color of shells, with clear border and surface contour. To find the abnormal blood vessels more clearly, we can use the green filter. High-grade lesion shows rough mosaic and rough punctation or both. In addition, finding the cervical blood vessels can help us to determine high-grade lesion. By understanding the description of the epithelial cervix and abnormal blood vessels , we will easily distinguish high-grade lesions from low grade lesion. Keywords: cervical precancer, colposcopy findings